Multiple imputation to deal with missing objectively-measured physical activity data: findings from two cohorts - Rafaela Costa Martins; Bruna Gonçalves C. da Silva; Cauane Blumenberg; Luiza Isnardi Ricardo; Shana Ginar da Silva; João Pedro Ribeiro; Alicia Matijasevich; Ana Maria Baptista Menezes; Helen Gonçalves; Fernando César Wehrmeister; Iná dos Santos; Inácio Crochemore-Silva; et al. (Revista Brasileira de Atividade Física e Saúde)
The objective of this article was to describe patterns of losses of information regarding accelerometer data and to assess the use of multiple imputation to generate physical activity estimates for individuals without accelerometry data. Two birth cohort studies from Pelotas (Brazil) with participants aged 22 and 11-years old assessed objectively measured physical activity differences between complete and imputed cases. Mean values of overall physical activity for complete cases (n1993 = 2,985 and n2004 = 3,348) and for complete cases plus imputed cases (n1993 = 760 and n2004 = 79) were described according to predictors. Male individuals, participants with black skin color, and less schooled individuals presented higher averages of overall physical activity than their counterparts. Almost all imputed estimates were comparable to the complete cases, and the highest difference found was 0.7 mg for the first quintile of socioeconomic status of the 1993 birth cohort. Multiple imputation is a positive technique to deal with missing data from objectively measured physical activity. It provides a set of relevant variables to be used in order to efficiently predict accelerometer data.